2013
DOI: 10.3928/23258160-20121221-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of the Dexamethasone Intravitreal Implant in Vitrectomized and Non-vitrectomized Eyes With Macular Edema Secondary to Central Retinal Vein Occlusion

Abstract: This retrospective study shows similar CMT reductions with DEX implant treatment for CRVO-related macular edema in vitrectomized and non-vitrectomized eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Although similar results of comparison between non-PPV and PPV eyes have been reported in ME associated to CRVO, 18 this series is, to the best of our knowledge, one of first to report a comparative study between non-PPV and PPV eyes with uveitic ME treated with DEX-intravitreal implant. In our series, non-PPV eyes had greater risk of developing IOP increase and therefore, should have closer IOP monitoring after DEX-intravitreal implant injection.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Although similar results of comparison between non-PPV and PPV eyes have been reported in ME associated to CRVO, 18 this series is, to the best of our knowledge, one of first to report a comparative study between non-PPV and PPV eyes with uveitic ME treated with DEX-intravitreal implant. In our series, non-PPV eyes had greater risk of developing IOP increase and therefore, should have closer IOP monitoring after DEX-intravitreal implant injection.…”
Section: Discussionsupporting
confidence: 67%
“…Similar results have been reported in DEX-intravitreal implant for treatment of ME secondary to central retinal vein occlusion (CRVO). 18 Although the implant avoids systemic side effects, rise in IOP was the most common complication. Statistical analysis of IOP during all follow-up showed a higher IOP in non-PPV eyes compared with PPV eyes with statistically significant differences from third to 12th month.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit‐studies have shown no difference in clearance rates of DII in vitrectomised and non‐vitrectomised eyes . The efficacy of DII has also been shown to be similar in vitrectomised and non‐vitrectomised eyes when used to treat macular oedema secondary to CRVO …”
Section: Steroid Preparations and Methods Of Local Administration To mentioning
confidence: 99%
“…We hypothesized that the DEX implant would be a useful intraoperative adjunct to ERM peeling because its greater potency and prolonged exposure time compared to IVTA may be more effective at improving outcomes in the post-vitrectomy eye. [28][29][30] Prior reports of the use of DEX for ERM surgery have been limited to the management of refractory postoperative CME after PPV with ERM peeling. 31,32 In this study, we focused on the prophylactic placement of DEX to hasten and improve the therapeutic endpoint of normalized macular contour.…”
Section: Discussionmentioning
confidence: 99%